La auditoría de cumplimiento y su incidencia en la gestión pública del centro técnico productivo (CETPRO) en Loreto 2023 - Sifuentes Rojas, Jervis Christopher (2025)
The purpose of this research was to determine whether compliance auditing has an impact on the management of the Centro Técnico Productivo (CETPRO) in Loreto, 2023. A quantitative, applied, descriptive and explanatory approach was used, and the research design was correlational. Surveys and files were used as a means of recording methods of analysis in a document. The sample consisted of 57 people. The results showed that, with respect to compliance auditing, the majority of respondents reported that it exists (56.1%), while a medium percentage indicated that it does not (31.6%) or do not know, do not think (12.3%). This indicates that, according to the established evaluation criteria, the perception of compliance auditing and its impact on the entity is at a high level. In conclusion, a majority of respondents (56.1%) consider that a compliance audit does exist, which translates into a positive perception of its presence and impact within the School Feeding Committee. This reflects a high level of trust in audits and their effectiveness, which contributes to the transparency and effectiveness of the committee's operations.